Genetic parameters of body weights and prediction of mature body weight in Murrah buffaloes - JP Gupta; GK Sachdeva; RS Gandhi (Journal of Livestock Biodiversity, 2025)
Data on body weights of 725 Murrah buffaloes from birth to 30 months of age at six monthly intervals were recorded. Heritability of body weights at birth, 12 months and 30 months of age were moderate to high and significant. There were high and significaveghere) correlations between body weight at 6 months, 12 months, 18 months, and 24 months with other body weights respectively. The phenotypic correlations between body weights at successive ages were found to be positive and highly significant.. Prediction equation based on 6-month body weight was chosen as the most appropriate with an accuracy of 46.90%.